Examining the most cost effectiveness methods of hiring instructor for lifelong learning program at community college in Malaysia - Md Shariff, Noorul 'Ain; Abdul Kadir, Suhaida; Idris, Khairuddin; Basri, Ramli (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
The aims of lifelong learning program at a Community College, Malaysia are to provide training and courses to Malaysian citizens to improve their standard of living, cultivate interest and educate the community to inculcate lifelong learning. This study examines the most cost-effective methods to hire instructors in the implementation of the programs by specializing in the field of sewing and fashion. There are three methods of hiring instructors: (i) by using an existing lecturer who teaches a full-time certification program, (ii) by hiring an external instructor (from the private sector) according to the course requirements and (iii) by hiring instructors to teach a full time course for the lifelong learning program also known as the Lifelong Learning Lecturer (LLL Lecturer). These three methods are studied to determine the most cost effective method of instructor employment. This study measures the effectiveness of the program based on participants' perceptions of cognitive, affective, psychomotor and economic aspects. While estimating program cost estimates using the Ingredient Model by Levin & McEwan (2001). The findings showed that by hiring Lifelong Learning Lecturer costs the highest, but shows the lowest in cost- effectiveness ratio. This proves to be the most cost-effective method in compared to others. Thus, an implication of these findings is that, cost-related proofs should be taken into account by the decision makers or stakeholders to determine future implementation of the program with the most cost-effective method.